2018
DOI: 10.3892/or.2018.6704
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock gene Per2 downregulation in non‑small cell lung cancer is associated with tumour progression and metastasis

Abstract: Period2 (Per2) is a key circadian clock gene, and its deregulation contributes to tumour development, including breast cancer. However, the biological function and clinicopathological significance of Per2 in non‑small cell lung cancer (NSCLC) remain unclear. The present study aimed to explore the role of Per2 and its relative clinical significance in NSCLC. To analyse Per2 expression in NSCLC specimens, reverse transcription‑quantitative polymerase chain reaction was performed, and the results indicated that P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 29 publications
4
30
0
Order By: Relevance
“…To explore the role of the classical circadian gene PER2 in OSCC, we performed this study and revealed that PER2 expression and nucleus-translocation were both downregulated in OSCC tissues and cells as well as ANT. Similar to the results in non-small-cell lung cancer [20], PER2 overexpression significantly inhibited the proliferation, migration, and invasion of OSCC cells, indicating that PER2 might act as a crucial antitumor gene. e growth of in vivo tumors was also suppressed resulting from the upregulation of PER2 in derived OSCC cells.…”
Section: Discussionsupporting
confidence: 83%
“…To explore the role of the classical circadian gene PER2 in OSCC, we performed this study and revealed that PER2 expression and nucleus-translocation were both downregulated in OSCC tissues and cells as well as ANT. Similar to the results in non-small-cell lung cancer [20], PER2 overexpression significantly inhibited the proliferation, migration, and invasion of OSCC cells, indicating that PER2 might act as a crucial antitumor gene. e growth of in vivo tumors was also suppressed resulting from the upregulation of PER2 in derived OSCC cells.…”
Section: Discussionsupporting
confidence: 83%
“…A few studies have exemplified that the expression of the circadian clock gene Per2 is markedly downregulated in non-small cell lung cancer, breast cancer, ovarian cancer, gastric cancer, colorectal cancer and liver cancer [17-19, 22, 23], and it is tightly connected to the occurrence and development of cancer. Xiang et al reported that overexpression of Per2 distinctly inhibits tumor cell growth, migration and invasion [12,19,24]. Previous studies have also reported that overexpression of Per2 promotes apoptosis and inhibits proliferation in glioma, breast, leukemia and lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins encoding by PER2, GADD45A, and TPD52 genes are also involved in the cancer cell proliferation and tumor growth and are dysregulated in cancer cells (Wang et al 2016;Xiang et al 2018;Xiong et al 2018;Zhang et al 2018;Hu et al 2019;Rahman et al 2019). At the same time, the expression of these genes was resistant to the silencing of adipokine NAMPT in the glioma cells.…”
Section: Discussionmentioning
confidence: 99%